Statement Kebijaksanaan Moneter - Teguh Sihono (Universitas Negeri Yogyakarta, 2010)
Monetary policy at 2010 year like as statement and implemented by Indonesia Bank (BI), as a purpose to reach national economy development target. That is counted unemployment, inflation pressure, and suppress international balance payment deficit. The monetary policy influence the first time tasted by banking monetary sector and then tasted by real sector.The monetary policy transmission can influence economy activity pass through some strip that is: the cost of capital, wealth channel, portofolio theory, and monetary theory. The latest purpose of monetary policy is watch over and take care of stability of rupiah value the thing which reflected at low level and inflation stability. Mechanism of monetary policy the thing which implementation with rate BI policy for influence inflation pass through some strip among others; rate of interest, credit, exchange value, asset and expectation.Application Asean-China Free Trade Agreement (AC-FTA) expected has an positive impact, concerning domestic economy, inflation level indicate a little increase in early 2010 year, although still appropriate revolves around target Indonesia Bank (BI) as high as 5% in January month 2010 noted down 0,84% (mtm) or 3,72%, formerly 0,33% (mtm) or 2,78%. Domestic financial sector became better by watched over money market inter bank (PUAB) even lean to decrees. To optimal result of monetary policy it is always together with fiscal policy and coordinate inter Indonesia Bank (BI) with central government along with regional government